The effect of student activity in organizing, learning motivation and learning behavior on academic achievement of students of the faculty of economics and business, Bengkulu University - Frendi Pajar Juniko Simbolon (Institute of Computer Science (IOCS), 2024)
This study aims to determine the effect of student activeness in organizations, learning motivation and learning behavior on the academic achievement of students of the Faculty of Economics and Business, Bengkulu University. This research is descriptive research with quantitative research. The population of this study were students of the Faculty of Economics and Business, Bengkulu University class of 2020, 2021, 2022 and 2023 who participated in organizations inside and outside the campus environment. Sampling in this study used probability sampling technique with 100 students as respondents. The data collection technique used a questionnaire. The data analysis technique uses multiple regression analysis. The results showed that: (1) There is a positive and significant effect of student activeness in organizations on student academic achievement. (2) Learning Motivation has no positive effect on student academic achievement. (3) There is a positive and significant effect of learning behavior on learning achievement.